Efficacious and save use of biosimilar filgrastim for hematopoietic progenitor cell chemo‐mobilization with vinorelbine in multiple myeloma patients. Issue 1 (22nd March 2016) - Maul, Julia‐Tatjana; Stenner‐Liewen, Frank; Seifert, Burkhardt; Pfrommer, Sarah; Petrausch, Ulf; Kiessling, Michael K.; Schanz, Urs; Nair, Gayathri; Mischo, Axel; Taverna, Christian; Schmidt, Adrian; Bargetzi, Mario; et al.
Abstract : Biosimilars are increasingly being licensed as equipotent drugs, although efficacy and safety data are not available for all clinical indications. Accordingly, the efficacy of the biosimilar filgrastim Zarzio® combined with vinorelbine for chemo‐mobilization of CD34+ hematopoietic progenitor cells (HPC) in patients with multiple myeloma has not been evaluated yet. We compared the efficacy of vinorelbine combined with this biosimilar filgrastim for HPC mobilization to vinorelbine plus original filgrastim (Neupogen®). Overall, 105 multiple myeloma patients received vinorelbine 35 mg/m 2 intravenously on day 1 and either original filgrastim ( n  = 61;58%) or biosimilar filgrastim ( n  = 44;42%) at a dose of 5 µg per kg body weight (BW) twice daily subcutaneously starting day 4 until the end of the collection procedure. Leukapheresis was scheduled to start on day 8 and performed for a maximum of three consecutive days until at least 4 × 10 6 HPC/kg BW were collected. All patients proceeded to leukapheresis. In 102 (97%) patients the leukapheresis sessions were started as planned at day 8. The median number of collected HPC was 7.3 × 10 6 /kg BW (0.2–18.3) with original filgrastim compared to 9 × 10 6 /kg BW (4.2‐23.8) with the biosimilar filgrastim ( P  = 0.16). HPC collection was successful in 57 (93%) of 61 patients of the original group and in all 44 (100%) patients of the biosimilar group ( P  = 0.14). No differences were observed regarding side effects. Duration of neutrophil engraftment after autologous HPC transplantation was similar between the two groups ( P  = 0.17). Biosimilar and original filgrastim achieve comparable results in combination with vinorelbine regarding HPC mobilization and transplantation outcome in multiple myeloma patients. J. Clin. Apheresis 32:21–26, 2017. © 2016 Wiley Periodicals, Inc.